Performance Optimization of Hydraulic Type Load Frequency Control in Hydropower Plants: Study of Controllers with dan Without Droop Characteristics - Laksono, Heru Dibyo; Putri, Dhea Rahmadani; Muharam, Mumuh; Pratama, Rizki Wahyu (Fakultas Teknik Universitas Khairun, 2025)
This research discusses the performance of the hydraulic type Load Frequency Control (LFC) system in hydropower plants using a single controller configuration equipped with a governor against power input. The Load Frequency Control (LFC) system is used to stabilizer the power frequency during load changes by considering the influence of droop characteristics on the governor. Analysis is performed using MATLAB simulation to measure transient parameters such as rise time, peak time, steady state time, and maximum skip. The results show that the use of droop on the governor is more effective in reducing overshoot, improving system stability, but slowing down the response time. Conversely, the configuration without droop accelerates the system response but risks overshoot. Controllers with derivative components such as PD and PDF, are superior in achieving rise time. Whereas, controllers that have integral components such as PI, PID, and PIDF are better at controlling overshoot when using droop characteristics. In conclusion, the combination of droop characteristics with derivative components in the governor provides optimal performance in maintaining the frequency stability of the hydraulic type Load Frequency Control (LFC) system.